Cellular models to study the emergence, expansion and differentiation of pancreatic progenitor cells in vitro - Plumb, Colin Anthony (The University of Edinburgh, 2019)
Cell transplantation of pancreatic islets has been proven to be an effective long-term treatment for Type 1 diabetes. However, the lack of sufficient cadaveric donor tissue has prevented widespread clinical adoption of cell therapy. An alternative source of cells would be hugely beneficial in overcoming this donor shortage. Cells of the islets arise during development from a shared precursor cell – the NGN3+/NEUROD1+ pancreatic endocrine progenitor. Over the past decade, human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) have been the main focus for providing an alternative source of pancreatic cell types for transplant. While differentiation to PDX1+/SOX9+ early pancreas progenitor cells has been successful, efficient differentiation to endocrine progenitors and mature islet cells has not been achieved. This suggests that we lack the knowledge to correctly and effectively specify an endocrine fate in hES-derived pancreas cells. It was the aim of this thesis to describe simple methods for culturing authentic pancreas progenitor cells from mouse and human foetal pancreas tissue, with which we could study the biology of these progenitor cells to ultimately inform better hESC differentiation protocols, and which may also be useful for cell therapy in their own right. To achieve these aims, we have taken three approaches. First, we provide characterisation of early pancreas progenitors during human foetal pancreas development, and how expression of key markers changes over time. Second, we describe methods for isolating and expanding mouse and human foetal pancreas progenitors, producing new cellular models with which to investigate the specification of endocrine cell fate. Finally, we generated an hESC reporter line to allow for easier identification of conditions that induce hESC-derived pancreatic endocrine progenitors in vitro. We have described the precise timing of the transition from early pancreas progenitor to endocrine progenitor in the developing human and mouse foetal pancreas. Using this information, we have pinpointed the stages of foetal development when mouse and human have the maximum potential proliferative capacity. Using samples from these developmental stages, we demonstrate that PDX1+/SOX9+ human and mouse foetal progenitors can be isolated and expanded long-term in monolayer in defined conditions. Cultured mouse foetal pancreas progenitors can be induced to differentiate to endocrine progenitors in vitro. We also generated a novel NGN3- GFP/CyclinB1-Cherry hESC reporter line, which allows identification of emerging endocrine progenitor cells and their proliferative capacity. The new cellular models presented here are ideally suited for many downstream applications including high-throughput pharmacological screens and imaging assays. Studies using these systems will help improve our understanding of human pancreatic endocrine progenitor specification and harness these cells in new types of cell therapies for diabetes.
Keywords: β-cells; insulin; islet transplant; human embryonic stem cells; hESCs; pancreas stem cells; diabetes